Two new Tytthoscincus Linkem, Diesmos, & Brown (Squamata; Scincidae) from Peninsular Malaysia and another case of microsyntopy between ecologically specialized, unrelated, leaf-litter species - Grismer, L. Lee; Wood, Perry L. Jr.; Ahmad, Amirrudin B.; Baizul-Hafsyam, B. S.; Afiq-Shuhaimi, M.; Rizal, Syed A.; Quah, Evan S. H. (Zootaxa, 2018)
Two new species of diminutive, sympatric, lowland, leaf-litter skinks of the genus Tytthoscincus Linkem, Diesmos & Brown from the Sekayu region of Hulu Terengganu, Terengganu State in northeastern Peninsular Malaysia are described on the basis genetic and morphological data. One of the new species, T. monticolus sp. nov., was collected in a hilly riparian area along Sungai (=river) Bubu and is most closely related to an undescribed species from the Tembak Reservoir area. The other, T. keciktuek sp. nov. collected along Sungai Peres, is most closely related to T. perhentianensis Grismer, Wood, & Grismer from Pulau (=island) Perhentian Besar. Sympatry and syntopy of multiple, specialized, unrelated, leaf-litter species of Tytthoscincus was previously only known from upland areas and these new species represent the first example of lowland of sympatry. More importantly, however, these endemic species add to a growing body of research and discoveries that continue to underscore the unrealized biodiversity of the riparian systems of Hulu Terengganu and the Sekayu region and their need for protection and continued study.